Vendors as Environmental Stakeholders: Lessons from a Regional Sports Event event - Joo-Ee Gan (ASEAN Journal on Hospitality and Tourism, 2020)
This paper examines the impact of vendor management on the recycling programme of a regional sports event. Guided by the theory of planned behaviour (TPB) and the norm activation model (NAM), the organizer's leverage strategies were qualitatively assessed for their effectiveness in promoting vendor recycling behaviour. The findings identified vague selection criteria, unclear expectations, limited engagement, the lack of communication and poor coordination as weaknesses in the organizer's leverage strategies. In particular, the altruistic strategy of information dissemination "“ deployed infrequently and unaided by utilitarian measures such as economic incentives and formal sanctions "“ did not encourage recycling behaviour. The impact of social influence showed that subjective norms were not merely a predictor of behaviour (as per the TPB), they influenced the NAM's dual-criteria, namely, awareness of consequences and ascription of responsibility. The absence of back-of-house disposal facilities, inconsistent bin system, poor labelling of the recycling bins and infrequent bin clearance significantly lowered the vendors' recycling rate. More importantly, convenience was found to influence norm activation, in that inefficient recycling logistics furnished the vendors with an excuse not to recycle. Thus, convenience was not merely as an aspect of TPB's perceived behavioural control, this determinant influenced personal norms. Where weak environmental norms prevail, it may be necessary to impose formal sanctions to enforce recycling, even though formal sanctions cannot ensure lasting recycling behaviour.